Decomposed dicom video into frames using matlab - Arshad, S.A. (Asian Research Publishing Network, 2016)
Nowadays, the medical world has become more sophisticated and numerous changes have been made specially to ensure convenience and comfort of the medical field such as MRI machines, advanced angiogram and others medical equipment. The file format for this equipment is DICOM which used for handling, storing, printing, and transmitting information in medical imaging. Digital Imaging and Communication in Medicine (DICOM) is a standard for medical images and it's executed for medical equipment likes radiology, radiotherapy and cardiology. The advantage of using DICOM is it allowed connectivity of engineering information to exchange images and info within the hospital and telemedicine. In this paper, the objective is to play DICOM video which taken from X-ray Angiography (XA) using multimedia format and decomposed it into frames by using MATLAB software. The purpose is to make the physician display the video in single frame and as a result to get better view of diseases and improved the efficiency and diagnose quality better. Â©2006-2016 Asian Research Publishing Network (ARPN).